Efektifitas Strategi Pemasaran Kopi Luwak Arabika “Rollaas” Terhadap Volume Penjualan Pada PT. Rolas Nusantara Mandiri - Surabaya - Dwi Nisa Widhawati; Achmad Daengs GS (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
Luwak Coffee is one of excellent coffee products. Luwak Coffee was first discovered in Indonesia. At the beginning of the discovery of civet coffee, mongoose manure (Paradoxorus hermaphroditus) was obtained from the coffee garden directly. Along with the development of the age and the increasing demand of civet coffee, civet droppings are no longer obtained from wild mongoose in the garden but derived from civet droppings that eat coffee beans in the cage that has been provided  civet coffee producers. PT Rolas Nusantara Mandiri is one of the companies that sell arabica civet coffee with the brand “ROLLAAS”. PT Rolas Nusantara Mandiri markets its products by applying 4P marketing mix. Pricing adjusted market prices and production costs, which is to build a networkof sales of mongoose coffee in the country, provide discount for promotion. The implementation of 4P so far has not fulfilled the company’s expectation that the target every month during 2016-2017 is still not reached. With that is necessary research conducted to  determine the extent to which 4P applied company can affect the sales volume and effectiveness of marketing strategies undertaken. The results of this study indicate that influential variables are variable price, and promotion. There are several determinants of the possitive effect of price on sales volume. The possitive value of the price coefficient is due to a one-time price change and has not had a major effect on sales. Coefficient possitive values can be interpreted that there needs to be additional promotional costs if the company wants to fulfill the target. The effectiveness of marketing strategy that has been applied can be seen from the value of target fulfillment percentage. The percentage of target fulfillment is obtained from the comparison of realization with the  specified target. There are still many sales targets that can not be fulfilled in 2016-2017. While the effectiveness in the mid-year months tend to have low effectiveness value. The uneveness of achievement of target every month must be solved immediately, so that the company can get income as expected or target. If the target is not met it will affect the company’s revenue